El Despido Incausado y Fraudulento Laboral - Catacora Santisteban, Percy Alberto (2017)
The research in question, is to overcome the difference in the concerned worker can get their compensation or reinstatement to the workplace, having been dismissed as uncaused and fraudulent, this allows us to consider that having legal ways for the employers can reduce the number of workers for economic losses, extraordinary contingencies that do not support the number of workers initially anticipated at the time of the business establishment or because with the passage of time has broken the identification and trust between employers and employee. Often the employer, in a improntus that is not right, reacts facto and without complying with the legal bases that provided by law, dismisses the worker, harming the interests of the server, causing a problem with social consequences.